Identification and partial characterisation of locally isolated lipolytic bacteria - Meng, Liu (2011)
Biodiesel methyl esters)is a clean alternative fuel which can be produced from many renewable resources.It is regarded as the fuel of the future and it has the advantages of being biodegradable and non-toxic.Palm oil,like other vegetable oils,can be used as feedstock for biodiesel production.It is processed through transesterification to produce palm oil methyl ester.Enzymatic reactions catalyzed by lipases are potentially excellent processes to produce biodiesel through the transesterification reaction.Enzymes have several advantages over chemical catalysts such as mild reaction conditions,high specificity,and renewability.The production of biodiesel using a biocatalyst eliminates the disadvantages of the alkali process by producing a product of very high purity.Various microorganisms like bacteria and fungi produce different kinds of enzymes which could be used as catalysts in a series of degradation reactions,such as transesterification.In this study,eighteen(18)bacterial strains were successfully isolated from local soil samples and some of their characteristics determined.The optimum temperatures of all strains were in the range of 30 to 37oC, and the optimum batch culture times of all strains be were in the range of 24 to 48 hours.All strains were submitted for Gram-staining.Three(3)strains denominated as A, B and C that were involved in the most significant transesterification reaction were selected for identification by submitting them to biochemical tests using the commercial API kit.The same three(3)isolates were submitted to identification by molecular technique.Two bacteria were identified to be Pseudomonas geniculata(A)and Stenotrophomonas maltoplilia(C),while the second bacteria(B)failed to be identified.Enzymatic transesterification of crude palm oil with methanol was studied.The enzymes from the three bacterial strains with the most significant transesterification reactions were tested for yield of biodiesel by changing the molar ratio of alcohol to crude palm oil and by changing reaction temperature. The molar ratio of methanol to crude palm oil was varied in the range from 3:1 to 4:1.The reaction temperature was varied from 35oC to 60oC.It was found that the optimum ratio of methanol to crude palm oil is 3:1 and the optimum reaction temperature is 40oC.